Mixed method in political communication research: the study of media usage & voting behavior as a case analysis - A. Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha (Universiti Kebangsaan Malaysia (UKM), 2017)
The study of political communication has expanded in recent decades, concurrent with the emphasis on examining the state of the field, but neglecting the examination on the research methodology employed in the field. While previous work in this area has mainly utilised a particular single methodology of either a quantitative or a qualitative approach, this paper discusses the application of mixed methods in political communication, by reviewing an example from the authors’ empirical study conducted on media usage and voting behaviour among youth in Malaysia. This paper discusses the advantages of using the mixed methods approach in political communication research, processes as well as challenges related to mixed method in relation to media and voting behaviour study. Implications of mixed method in political communication research are also discussed.